Energy harvesting for back-up power supply using speed humps - Khan , Umair Ahmad; Khan, Sheroz; Azman, Amelia Wong (IEEE, 2014)
Renewable energy is becoming a prosperous industry with numerous researchers focusing and exploring new and effective ways to harness the power from means available on spot. This paper presents a new proposed mechanism for harnessing from vehicles passing over ramps energy destined of going into waste if not harvested. It is kinetic energy used for generating electricity. Unlike the many other designs for power generation, this paper sheds light on the idea of the rotational conversion-using flywheel and gear mechanism used underneath the road surface at the point of road where a speed-breaker is raised. The linear motion of a rack is converted into rotational motion applied by the oncoming vehicular load. The system is described in terms of the dimensions of the rack and pinion and the number of teeth on the gears. The pulley structure is geared such it is ultimately making a generator to rotate for producing an output voltage. The output voltage is of variable nature depending on the traffic flow. The system is described on assumption of single vehicle passing by over a time interval of hence producing a power output as the vehicle is inputting a certain amount of energy in a given time interval. The analysis of the system is in terms of the related equations.